Can intra-articular daidzein injection reduce oxidative damage and early osteoarthritis in a rabbit temporomandibular joint model? - Gokce Elif Erdayandi; Onur Yilmaz; Gokcen Kerimoglu; Elif Sahin; Sedanur Yilmaz Dogan (BMC, 2024)
Abstract Background Oxidative damage and inflammatory cytokines in osteoarthritis (OA) exacerbate the disease course. Daidzein (DZ) has antioxidant and anti-inflammatory effects. This study evaluated the early histopathological effects of intra-articular daidzein injection on experimentally induced osteoarthritis in rabbit TMJs. Methods The predictor variable was intra-articular injection of DZ or a saline control. 50 µl of 3 mg/mL MIA solution was injected into the right TMJ of 16 New Zealand rabbits to induce experimental OA. One rabbit was sacrificed after 4 weeks to confirm the formation of the OA model and the OA model was obtained. The remaining 15 rabbits were randomly divided into 2 groups: an experimental group (9 rabbits) and a control group (6 rabbits). On days 1, 7, 14, and 21; 50 µl of saline solution was applied to the right TMJ of the control group and 50 µl daidzein solution (1.8 mg/ml) was applied to the right TMJ to the experimental group. After one week from the date of the last injection, the rabbits were sacrificed, and histopathological and biochemical evaluations were performed. The Shapiro-Wilk test was used to evaluate whether the variables in the study conformed to normal distribution. Mean ± SD (standard deviation) or median (interquartile range (IQR)) was used to show the descriptive statistics of the variables. T-test and Mann Whitney U test were used to compare the control and experimental groups for biochemical changes. The chi-square test was used to show the distribution of histopathological changes variables obtained within the scope of the study based on control and experimental groups. A P-value < 0.05 was considered significant for all evaluations. Results There were 8 and 6 animate treated with DZ and saline, respectively. There was no statistically significant difference between groups in articular cartilage (p = 0.3), osteochondral junction (p = 0.3), subchondral bone structure (p = 1.0) or chondrocyte appearance (p = 0.4). The experimental group showed significantly lower mean values for Total Oxidant Status (TOS) (p = 0.002) and Oxidative Stress Index (OSI) (p = 0.007). Conclusions An intra-articular DZ injection appears to show limited reduction of oxidative damage and early OA in the rabbit TMJ. DZ might represent a promising natural compound with beneficial effects in the management of TMJ-OA.